MARKETING STRATEGY AND MARKETING PLAN IN DAKSA LABORATORY MEDIK BUSINESS DEVELOPMENT PROJECT - Noviana Puspitasari; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Ketut Sunaryanto (Ikatan Dosen Menulis, 2024)
The Medical Laboratory as a medical support unit can provide information about laboratory aspects of specimens or samples whose testing is carried out in the laboratory. Medical laboratories are a necessity that can diagnose diseases and check body health. Medical Laboratory business opportunities are increasing and also competing with competitors of similar companies. For this reason, Daksa Medical Laboratory needs a marketing strategy to attract the interest of its customers so that customers choose to have an examination at Daksa Medical Laboratory. The aim of this research is to analyze marketing plans and develop marketing strategies in the Medical Laboratory Business. This study used qualitative research methods. Data collection techniques use literature studies, interviews and observations. The data that has been collected is analyzed thematically. The research results show that the marketing strategy planning for Daksa Medical Laboratory has been implemented very well. Strategic planning is carried out up to the long-term stage, according to business strategy and the lean business canvas model. Marketing planning is carried out in stages of goals and objectives, marketing strategy, marketing mix, sales activities, scenarios and assumptions and sales projections.